BOARDING SCHOOL PROGRAM FOR MARRIED COUPLES BASED ON ISLAMIC CHARACTER AND ADAB - Hasan, Nur (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
This study explores the implementation and impact of a Pesantren Kilat (short-term Islamic boarding school) program specifically designed for married couples, with a focus on character building and Islamic manners (adab). Conducted over a one-week intensive period at a religious educational institution, the program aimed to instill values of patience, respect, effective communication, and emotional maturity in family life. The study found that participants experienced significant improvements in their understanding of marital roles, self-awareness regarding behavior, and conflict resolution. Activities such as reflective discussions, simulations, and spiritual learning were effective in strengthening moral character and enhancing relational harmony between spouses. The research emphasizes that character education integrated with Islamic values not only improves individual conduct but also contributes to a more harmonious household. The program demonstrated that a values-based approach to marriage education can serve as a foundation for cultivating strong, respectful, and emotionally intelligent family relationships. These findings support the notion that moral development within the context of Islamic boarding education is a vital strategy in reinforcing marital stability and societal well-being.